Transcriptional provirus silencing as a crosstalk of de novo DNA methylation and epigenomic features at the integration site - Senigl, Filip; Auxt, Miroslav; Hejnar, Jirí (Nucleic acids research, 2012)
The autonomous transcription of integrated retroviruses strongly depends on genetic and epigenetic effects of the chromatin at the site of integration. These effects are mostly suppressive and proviral activity can be finally silenced by mechanisms, such as DNA methylation and histone modifications. To address the role of the integration site at the whole-genome-scale, we performed clonal analysis of provirus silencing with an avian leucosis/sarcoma virus-based reporter vector and correlated the transcriptional silencing with the epigenomic landscape of respective integrations. We demonstrate efficient provirus silencing in human HCT116 cell line, which is strongly but not absolutely dependent on the de novo DNA methyltransferase activity, particularly of Dnmt3b. Proviruses integrated close to the transcription start sites of active genes into the regions enriched in H3K4 trimethylation display long-term stability of expression and are resistant to the transcriptional silencing after over-expression of Dnmt3a or Dnmt3b. In contrast, proviruses in the intergenic regions tend to spontaneous transcriptional silencing even in Dnmt3a(-/-) Dnmt3b(-/-) cells. The silencing of proviruses within genes is accompanied with DNA methylation of long terminal repeats, whereas silencing in intergenic regions is DNA methylation-independent. These findings indicate that the epigenomic features of integration sites are crucial for their permissivity to the proviral expression.
Keywords: genetická transkripce; Epigenesis, Genetic; Humans; DNA Methyltransferase 3B; DNA (Cytosine-5-)-Methyltransferases; DNA-(cytosin-5-)methyltransferasa; DNA-methyltransferasa 3B; Transcription, Genetic; lidé; proviry; epigeneze genetická; Gene Silencing; DNA Methylation; metylace DNA; umlčování genů; DNA Methyltransferase 3A; DNA methyltransferasa 3A; Alpharetrovirus; nádorové buněčné linie; integrace viru; Cell Line, Tumor; Virus Integration; Proviruses